A Study of Service Quality on Customer Satisfaction and its Impact on Customer Loyalty: The Case of Food and Beverage Industry in Bandung - Danurdara, Ananta Budhi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The purpose of this study was to determine the effect of service quality on customer satisfaction and its impact on customer loyalty. The research was conducted in the food and beverage industry sector in the city of Bandung. Participants in this study were customers in the culinary industry in the city of Bandung, with a total of 135 respondents. The data that has been collected was analyzed using path analysis. The results showed that there was an influence between service quality and customer satisfaction. There is an influence between service quality and customer loyalty. Job satisfaction also affects customer loyalty positively and significantly. Job satisfaction is able to mediate the relationship between service quality and customer loyalty. It is recommended that the food and beverage industry in the city of Bandung improve the quality of service, and also increase customer satisfaction.